Primitivism in Early 20th Century French Music: Darius Milhaud’s La creation du monde - Rucsanda, M.D.; Karacsony, N. (Universitatea Transilvania Brasov, 2024)
The first decades of the 20th century, particularly the post-war era, brought about numerous philosophical and cultural changes. Exoticism and orientalism were concepts that still governed arts and music, however the philosophical concepts that lay beyond the use of exotic or oriental themes was gradually altered. Exoticism represented more than the possibility for artists to create an idealized elsewhere, inspired by the contact with foreign cultures and their artistic products. It also offered artists the opportunity to express the complex meaning of various symbols associated with exoticism. In this context, Western society gradually turned toward a new aesthetic that could provide artists with an apparent connection to the roots of mankind. Primitivism, associated with folk art and mythology, represented a utopic state, prior to civilization or colonialism, but at the same time, it offered the possibility to explore certain archetypal symbols and express their possible meaning through art. Art nègre, represented by African and African American art and music, was most often associated with this aesthetic of primitivism, and influenced the works of Western artists. French composer Darius Milhaud returns to the theme of origins and creation in the work La création du monde, which combines elements associated with the concept of primitivism, with jazz music and Western compositional techniques.
Keywords: primitivism; African art; jazz; rhythm; French